Switching attacks in wireless networks using denial of service phenomenon (International Journal of Engineering and Computer Science, 2014)
sensor  networks  offer  eco- nomically viable solutions for a variety of applications. for example, current implemen- tations  monitor  factory  instrumentation, pollution levels, free- way trafﬁc, and the structural integrity of  buildings.  other  applications include climate sensing and control in office  buildings  and home  environ- mental sensing systems for tempera- ture, light, moisture, and motion.  ad-hoc low-power wireless networks are an exciting research direction in sensing and pervasive computing. prior security work in this area has focused primarily on denial of communication at the routing or medium access control levels. this paper explores resource depletion attacks at the routing protocol layer, which permanently disable networks by quickly draining nodes’ battery power. these “vampire” attacks are not specific to any specific protocol, but rather rely on the properties of many popular classes of routing protocols. we find that all examined protocols are susceptible to vampire attacks, which are devastating, difficult to detect, and are easy to carry out using as few as one malicious insider sending only protocol compliant messages.